Mothers and mother tongue : their role in promoting Foochow to their children - Ting, Su Hie; Hung, Yu Ling (2008)
Research in settings where the Foochow population is small relative to other ethnic groups has indicated a shift away from Foochow towards Mandarin and English and the question raised is whether the same phenomenon is happening in Foochow-dominant settings. The study examined whether Foochow mothers promote use of the mother tongue by their children in Foochow-dominant towns in Sarawak. Interview data were collected from 30 participants from seven families, of which 14 were mothers. The results showed that the children's language use was in the hands ofthe mother more than the father although some Foochow mothers allowed the family situation to dictate the children's first language. Others took on a more active role in deciding the language(s) their children should learn, some going with and others going against the tide of social change. The demographic profiles ofthe families were examined to find out the factors influencing Foochow mothers to promote or demote their ethnic language in the family.